Battles for memory: on the issue of memorializing the name of Admiral A. V. Kolchak in Omsk - A. V. Sushko; D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
In this work, from the point of view of historical and cultural studies, the issue of memorialization in Omsk in memory of Admiral A. V. Kolchak is analyzed. This question is considered from the standpoint of modern political history of the national and local levels in relation to the development of history as a science and the process of forming the historical memory of the Civil War. The role of specific people who influenced the course of these phenomena in Omsk is highlighted. According to the authors, the example of Omsk clearly shows that sharp controversy and an ambiguous assessment of the events of the Civil War remains in modern Russian society